2018
DOI: 10.1007/s12098-018-2752-7
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Chronic Hepatitis C Infection with Direct Acting Antivirals in Adolescents with Thalassemia Major

Abstract: Generic DAAs are effective and safe in TM adolescents with HCV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 18 publications
2
25
0
Order By: Relevance
“…In total, 39 references met the inclusion criteria. Twenty‐eight papers were published as full‐text articles 3‐8,11‐32 and 11 as abstracts 33‐43 . Two studies were randomised clinical trials, 27,33 whereas all the other studies were nonrandomised studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 39 references met the inclusion criteria. Twenty‐eight papers were published as full‐text articles 3‐8,11‐32 and 11 as abstracts 33‐43 . Two studies were randomised clinical trials, 27,33 whereas all the other studies were nonrandomised studies.…”
Section: Resultsmentioning
confidence: 99%
“…All studies were at low risk of bias in classification of interventions, measurement of outcome and selection of the reported result (Appendix A2). Regarding bias due to deviations from intended interventions, 13 studies were judged at moderate risk 4‐8,11,14,21,24,30,35,40,42 and one at serious risk 41 . As for bias due to missing data, five studies were considered at moderate risk 5,8,14,24,40 and four at serious risk 30,35,38,41 .…”
Section: Resultsmentioning
confidence: 99%
“…Other minor negative side effects included headache and nausea. Nagral et al explored the efficacy and safety of DAAs in adolescents with thalassemia major. Regimens included SOF/LDV and SOF/DCV with two patients in the latter group also receiving RBV.…”
Section: Summary Of Studies Treating Hcv Using Daas In Patients With mentioning
confidence: 99%
“…Recently, Sharara et al reported 100% SVR with the pangenotypic single‐tablet combination of SOF/velpatasvir (VEL), and no adverse events in seven patients with genotype 4 HCV infection. Table summarizes the literature on various DAA regimens in the thalassemia population …”
Section: Summary Of Studies Treating Hcv Using Daas In Patients With mentioning
confidence: 99%
“…This combination resulted in an SVR of around 52% in patients infected with HCV GT 1 and 4, and 89% in those infected with HCV GT 2 and 3, but was associated with significant side effects ( 54 56 , 58 ). Compared to IFN-based regimens, DAAs not only are more efficient but also have fewer side effects ( 10 12 , 15 17 , 22 , 24 26 , 28 , 29 , 31 , 34 39 ). We found that the overall SVR12 rate for the adolescents and children treated with DAAs was 99.4 and 98.9%, respectively, although the frequency of AEs was substantial (34.7 and 51.6%).…”
Section: Discussionmentioning
confidence: 99%